От составителя [“In memoriam: Larisa Georgievna Stepanova (1941—2009).” Section Editor’s Note] - Levinton, Georgy (Slavica Revalensia, 2021)
This is a brief introduction to a section dedicated to the memory of a renowned Russian expert in Italian Studies Larisa Georgievna Stepanova (1941—2009).